Catherine Malabou’s Plasticity in Translation - Shread, Carolyn (TTR)

(untitled) (Association canadienne de traductologie, 2011)
Translating Catherine Malabou’s La Plasticité au soir de l’écriture: Dialectique, destruction, déconstruction (2005) for its 2009 English publication, I was struck by how suggestive Malabou’s concept of plasticity is for a reworking of conventional notions of translation. In this philosophical autobiography of her encounters with Hegel, Heidegger, and Derrida, Malabou introduces “plasticity,” suggesting that the more contemporary notion of plasticity supersede Derrida’s proposal of writing as motor scheme. Reviewing and developing Derrida’s innovative discussions of translation, this article argues that the giving, receiving, exploding, and regenerating of form described by plasticity changes change, and therefore alters the transformation that is translation. Adapting Malabou’s philosophical concept to the field of translation studies, I make a distinction between elastic translation and plastic translation, which allows us to break free of paradigms of equivalence that have for so long constrained translation theories and practice. While plasticity drives Malabou’s philosophical intervention in relation to identity and gender, it also enables a productive reconceptualization of translation, one which not only privileges seriality and generativity over narratives of nostalgia for a lost original, but which also forges connections across different identity discourses on translation.